The Strategies in Translating Indonesian Cultural Terms in Pramoedya Ananta Toer’s Footsteps - Gina Istiqomah (Passage, 2019)
This study investigated some strategies applied by the translator in translating Indonesian cultural terms found in the novel Footsteps. The data were taken from the original version of the novel entitled Jejak Langkah and its English version entitled Footsteps. By using qualitative method, this study classified and analyzed the data based on Newmark’s (1988) cultural categories and Venuti’s (1995) domestication and foreignization strategies in translation. The result showed that domestication and foreignization strategies were applied by the translator to translate Indonesian cultural terms with the percentage of 26.92% (domesticated) and 73.08% (foreignized). The most frequently used strategy by the translator in translating the cultural terms make the translation result to be less fluent and less transparent. However, it could make the target language readers feel closer to the nuance of the original story of the novel Footsteps and recognize linguistic and cultural differences of other languages, in this case Indonesian.Keywords: Domestication, Foreignization, Strategi Penerjemahan, Istilah Budaya.